Phospholipase A2 as a point of care alternative to serum amylase and pancreatic lipase. Issue 23 (26th May 2016) - Liu, Nathan J.; Chapman, Robert; Lin, Yiyang; Bentham, Andrew; Tyreman, Matthew; Philips, Natalie; Khan, Shahid A.; Stevens, Molly M.
Abstract : A lateral flow device for point of care measurements of phospholipase A2 group IB concentration is presented. Results from the device are found to correlate with serum amylase and pancreatic lipase levels. Abstract : Acute pancreatitis is a relatively common and potentially fatal condition, but the presenting symptoms are non-specific and diagnosis relies largely on the measurement of amylase activity by the hospital clinical laboratory. In this work we develop a point of care test for pancreatitis measuring concentration of secretory phospholipase A2 group IB (sPLA2 -IB). Novel antibodies for sPLA2 -IB were raised and used to design an ELISA and a lateral flow device (LFD) for the point of care measurement of sPLA2 -IB concentration, which was compared to pancreatic amylase activity, lipase activity, and sPLA2 -IB activity in 153 serum samples. 98 of these samples were obtained from the pathology unit of a major hospital and classified retrospectively according to presence or absence of pancreatitis, and the remaining 55 were obtained from commercial sources to serve as high lipase ( n = 20), CA19-9 positive ( n = 15), and healthy ( n = 20) controls. sPLA2 -IB concentration correlated well with the serum activity of both amylase and lipase, and performed at least as well as either markers in the differentiation of pancreatitis from controls.